2018
DOI: 10.1534/g3.118.200509
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of GIT1 Impacts eNOS Activity To Aggravate sFlt-1–Induced Preeclampsia Phenotype in Mice

Abstract: Preeclampsia, a serious multisystem disorder specific to human pregnancy, remains a considerable burden of disease worldwide. Reduced nitric oxide bioavailability is proved to be crucial in the maternal and fetal pathophysiology of preeclampsia. G-protein-coupled Receptor Kinase Interactor-1 (GIT1) is a novel endothelial nitric oxide synthases (eNOS) interactor mediator. The aim of this paper is to investigate the effect of GIT1 on preeclampsia. Blood pressure (BP) was measured using a carotid catheter-calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…GIT1, a GTPase-activating protein, plays a crucial role in regulating the biological activity of endothelial nitric oxide synthase (eNOS) [ 68 ]. The absence of GIT1 seems to aggravate PE-like phenotypes in mice by impeding NO production through suppression of eNOS activity [ 69 ].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…GIT1, a GTPase-activating protein, plays a crucial role in regulating the biological activity of endothelial nitric oxide synthase (eNOS) [ 68 ]. The absence of GIT1 seems to aggravate PE-like phenotypes in mice by impeding NO production through suppression of eNOS activity [ 69 ].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…4 The activity of eNOS is regulated by varieties of factors including post-translational phosphorylation, eNOS coupling, and the interaction of proteins. 5 Our previous studies indicated that low androgen status inhibited eNOS phosphorylation in corpus cavernosum of rats resulting in decreased NO production and impaired erectile function. 6 eNOS dimer formed by the coupling of eNOS monomer produces NO relaxing smooth muscle cells, while the uncoupling of eNOS produces superoxide radical (O 2 − ).…”
Section: Introductionmentioning
confidence: 98%
“…Nitric oxygen (NO) catalyzed by eNOS in endothelial cells plays a vital role in the initiation and maintenance of penile erection 4 . The activity of eNOS is regulated by varieties of factors including post‐translational phosphorylation, eNOS coupling, and the interaction of proteins 5 . Our previous studies indicated that low androgen status inhibited eNOS phosphorylation in corpus cavernosum of rats resulting in decreased NO production and impaired erectile function 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 In a rat model of preeclampsia, GIT1 knockdown can inhibit the activity of eNOS in the placenta and induce the exacerbation of the preeclampsia phenotype. 16 In a rat model of hepatic sinusoidal vascular endothelial injury, the expression level of GIT1 in vascular endothelial cells is decreased; the interaction between GIT1 and eNOS is weakened; and the activity of eNOS and the expression of NO is decreased. However, upregulation of GIT1 in damaged hepatic sinusoidal vascular endothelial cells can directly activate eNOS and considerably increase NO expression.…”
Section: Introductionmentioning
confidence: 99%